Investigation of Corrosion Resistance for Annealed and Hardened Stainless Steels. (7th July 2017) - Repukaiti, Reyixiati; Murkute, Pratik; Fast, Cody; Isgor, Burkan; Tucker, Julie
Abstract : Stainless steels are desirable for their good corrosion resistance and mechanical properties, and are widely used in marine applications that require high hardness. Heat treatment procedures increase the hardness of stainless steel, and affect microstructural, compositional and surface properties of these materials, hence affect their corrosion resistance. To investigate these relationships, a series of electrochemical, corrosion resistance, and mechanical tests at room temperature and ambient pressure were conducted on stainless steels that were exposed to simulated seawater conditions. Both annealed and hardened conditions were tested and evaluated during aforementioned tests. Preliminary salt solution spray tests have indicated that 2205 duplex stainless steel, 17-7 and 15-5 stainless steels have better corrosion resistance than other alloys in annealed condition. A series of electrochemical impedance spectroscopy (EIS) and cyclic polarization (CP) measurements were conducted on duplex 2205 stainless steel, 17-7 and 15-5 stainless steel in order to evaluate their corrosion resistance both in annealed and hardened conditions. The mechanisms that lead to changes in corrosion resistance due to heat treatment processes are discussed.